Herb Formula (GCis) Prevents Pulmonary Infection Secondary to Intracerebral Hemorrhage by Enhancing Peripheral Immunity and Intestinal Mucosal Immune Barrier - Yulu Miao; Bin Wang; Jing Hu; Hanyu Zhang; Xiaojin Li; Yingying Huang; Pengwei Zhuang; Pengwei Zhuang; Yanjun Zhang (Frontiers Media S.A., 2022)
Lung infection is a common complication induced by stroke and seriously affects the prognosis and life quality of patients. However, effective therapeutic strategies are still lacking. In the present study, the herb formula GCis was confirmed to prevent pulmonary infection induced by intracerebral hemorrhage (ICH). The animal model of lung infection induced by ICH, GCis (Ginseng Radix et Rhizoma, Aconiti Lateralis Radix Praeparata, and Cistanches Herba) was orally administrated every day for 7 days. Lung microbial biomass and pathological results showed that the GCis formula pretreatment significantly reduced lung bacterial biomass and alleviated pathological abnormalities. These results indicated that the GCis formula has a clear pharmacological effect on preventing lung infection induced by ICH. Immunosuppression induced by ICH seemed to be the main mechanism of lung infection. Our results showed that the spleen and thymus indexes, WBC, and LY% contents were significantly increased in the GCis formula group. Moreover, bone marrow cells were further analyzed by transcriptome sequencing, and GO and KEGG enrichment analysis results showed that immune function was the main pathway enriched by differential genes after GCis formula intervention. More importantly, our results showed that GCis pretreatment had no significant effect on the mRNA expression of IL-1β, IL-6, and TNF-α in the brain. These results indicated that the GCis formula could enhance immunity after ICH. The intestinal barrier function was further investigated in the present study, considering the origin of the source of infection. Our results showed that the mRNA expressions of intestinal ZO-1, SIgA, and MUC2 were significantly increased, villi structure was intact, inflammatory cell infiltration was reduced, and goblet cell number was increased after GCis formula treatment. These results suggest that the GCis formula can enhance the intestinal mucosal immune barrier. This study provides a herb formula (GCis) that could enhance peripheral immunity and intestinal mucosal immune barrier to prevent pulmonary infection induced by ICH. It would be beneficial in the prevention of severe clinical infections.